ANALISIS PENGARUH OPERATING LEVERAGE, FINANCIAL LEVERAGE DAN CASH FLOW TO SALES TERHADAP RETURN SAHAM PADA SEKTOR INDUSTRI TEKSTIL YANG TEDAFTAR DI BURSA EFEK INDONESIA - B11110104, Nofia Dian Kinasih (Jurnal Manajemen Update, 2015)
Investing is an activity postpone consumption or use of the funds at the present time in order to gain advantage in the future. Investments can be used by the company for growth in the distribution of wealth through investment returns to the appreciation of the value of investments or for other benefits for companies that invest, invest in investors faced with uncertainty (uncertainty) between the return that would be obtained with the risk that it will face. The greater the expected return akandiperoleh of investment, the greater the risk, so it is said that the return expectations are positively associated with risk. This research focuses on the Analysis of Effect of Operating Leverage, Financial Leverage and Cash Flow Return To Sales Of Shares on Textile Industry Sector Listed in Indonesia Stock Exchange. The problem in this study is whether the Operating Leverage, Financial Leverage and Cash Flow Return To Sales Of Shares on Textile Industry Sector Listed in Indonesian Stock Exchange. Techniques interpretation using purposive sampling with a sample of Textile Industry 9 Sector companies listed in Indonesian Stock Exchange during the period from 2009 to 2013, collecting data using secondary data published by the Indonesian Stock Exchange via the Internet. As for the use of analytical statistic techniques test using SPSS. The results of this study is concluded that the variable DOL, DFL and CFS partial and simultaneously the effect on stock return.   Key words :  Operating Leverage, Financial Leverage, Cash  Flow  To  Sales And Return Saham.